Maternal Neurobiological Processing of Negative Adolescent Stimuli: Relations With Positive Parenting and Relationship Quality. (22nd March 2019) - Turpyn, Caitlin C.; Niehaus, Claire; Faundez, Francisca; Thompson, James C.; Chaplin, Tara M.
Abstract : We examined associations between maternal affective neurobiology and positive parenting in a study of 20 mothers of adolescents. Mothers underwent functional magnetic resonance imaging during an emotion image task, rated parent‐adolescent relationship quality, and completed an adolescent interaction task in which positive parenting behaviors were observed. Maternal structure was associated with lower responsivity in emotional processing regions in the general negative image contrast and was related to greater dorsolateral prefrontal cortex activation to negative adolescent images. Parent‐adolescent relationship quality was associated with lower precuneus activation to negative adolescent images. Findings are among the first to connect functional brain processing with observed parenting behaviors for parents of adolescent children, and underscore the relative importance of affective processing in parenting older children.